The Integration of Webquest into English Learning: A Review Study - Ira Irzawati (Universitas Sarjanawiyata Tamansiswa, 2021)
In this pandemic era, integrating technological tools into teaching and learning activities is an ideal option to facilitate students in understanding and mastering English. Webquest is one of the web-based tools used in English learning. This study shed light on the use of Webquest in English learning through reviewing twenty journal articles to determine the effectiveness of utilizing Webquest in improving students’ English skills and components. ERIC, Academia, JSTOR, and Elsevier are the primary online database sources used in this study. The result of the investigation revealed that Webquest not only highly contributed to the enhancement of students’ listening, reading, speaking, and writing skills but also greatly supported the development of students’ grammar and vocabulary masteries. In short, Webquest is an ideal alternative learning tool to promote the development of students’ English skills and components.